2014
DOI: 10.1038/onc.2014.201
|View full text |Cite
|
Sign up to set email alerts
|

DACT2 is a functional tumor suppressor through inhibiting Wnt/β-catenin pathway and associated with poor survival in colon cancer

Abstract: Dapper homolog (DACT) 2 is one of the Dact gene family members, which are important modulators of Wnt signaling pathway. We aim to clarify its epigenetic inactivation, biological function and clinical implication in colon cancer. DACT2 was silenced in five out of eight colon cancer cell lines, but robustly expressed in normal colon tissues. The loss of DACT2 expression was regulated by promoter hypermethylation. Restoring DACT2 expression in colon cancer cell lines suppressed tumor cell growth by inducing cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 38 publications
6
48
0
4
Order By: Relevance
“…7C,D). Interestingly, β-catenin has been shown to interact directly with the three murine DACT paralogues (Kivimäe et al, 2011;Wang et al, 2015) and our data showed that a GFPtagged version of Dact2 (Dact2-GFP) and β-catenin colocalised in spherical intranuclear punctuate structures resembling nuclear bodies (Fig. 7C,D).…”
Section: Activity Of Dact1/2 Is Dispensable For Nc Cell Motilitysupporting
confidence: 48%
See 2 more Smart Citations
“…7C,D). Interestingly, β-catenin has been shown to interact directly with the three murine DACT paralogues (Kivimäe et al, 2011;Wang et al, 2015) and our data showed that a GFPtagged version of Dact2 (Dact2-GFP) and β-catenin colocalised in spherical intranuclear punctuate structures resembling nuclear bodies (Fig. 7C,D).…”
Section: Activity Of Dact1/2 Is Dispensable For Nc Cell Motilitysupporting
confidence: 48%
“…More recent data showed that these scaffold proteins can form complexes with β-catenin (Cheyette et al, 2002;Gao et al, 2008;Kivimäe et al, 2011;Wang et al, 2015), which is a key mediator of the Wnt signalling pathway (Clevers and Nusse, 2012). Although we do not rule out a contribution of DACT in non-canonical Wnt signalling, as previously shown in Xenopus embryos (Park et al, 2006;Wen et al, 2010;Kivimäe et al, 2011), our results show a strong and conserved inhibitory role played by DACT proteins in the canonical Wnt pathway.…”
Section: Reversible Inhibition Of Wnt/β-catenin Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, many of the down-regulated genes in both MLL3 and BAP1 knockout cells are known tumor suppressors, such as RBMS 3 35 , ITM2A 36 , GRHL2 37 , TCEA3 38 , DSC3 39 , FRZB 40 , and DACT2 41 (Fig 4f and Supplementary Fig. 6b, c).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to deletion, epigenetic modifications of DACT genes were also reported. For instance, DACT1 and DACT2 were reported to be methylated in hepatocellular carcinoma, oral squamous, gastric cancer, nasopharyngeal carcinoma, thyroid cancer, colon cancer and lung cancer (10,(26)(27)(28)(29)(30)(31). In addition, DACT3 was identified to have histone modifications in colorectal cancer (25,26,32).…”
Section: Discussionmentioning
confidence: 99%